2017
DOI: 10.1016/j.asjsur.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The significance of extended lymphadenectomy for colorectal cancer with isolated synchronous extraregional lymph node metastasis

Abstract: Findings from our study suggest that extended lymphadenectomy for colorectal cancer with synchronous isolated extraregional lymph node metastasis might be effective in carefully selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 15 publications
2
62
1
Order By: Relevance
“…After ruling out 277 duplicate publications, a further analysis involved 453 studies, out of which 406 were considered to not be relevant for titles and abstracts, while 47 full-text articles were assessed for eligibility. After removing 38 studies that did not comply with the inclusion criteria, nine studies (all retrospective, most of them being of good quality, see Supplementary material-Table S1) underwent qualitative synthesis [5,[10][11][12][13][14][15][16][17].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…After ruling out 277 duplicate publications, a further analysis involved 453 studies, out of which 406 were considered to not be relevant for titles and abstracts, while 47 full-text articles were assessed for eligibility. After removing 38 studies that did not comply with the inclusion criteria, nine studies (all retrospective, most of them being of good quality, see Supplementary material-Table S1) underwent qualitative synthesis [5,[10][11][12][13][14][15][16][17].…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…For example, Choi et al reported that the 5-year OS of the PALND group was significantly higher than that of the control group (53.4% vs. 12%, p = 0.045) [6]. Ogura et al reported that the 5-year cancer-specific survival was significantly higher in the R0 resection group than in the control group with palliative resection in patients with extra-regional lymph node metastasis [16]. Gagniere et al reported the outcome of radical retroperitoneal lymphadenectomy in patients with retroperitoneal nodal metastases from colorectal cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the average survival duration ( N = 6) for patients who undergo surgical resection after isolated PALN recurrence is 34 months, while that for patients who do not is 14 months [19]. In terms of comparative studies between experimental and control groups, one previous study was designed in a similar manner to ours but with a smaller number of patients [12]. Previous studies also demonstrated the effectiveness of para‐aortic lymphadenectomy but only in DG patients; no comparisons were made to NDG patients [9].…”
Section: Discussionmentioning
confidence: 99%